2022
DOI: 10.1371/journal.pone.0276478
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder engagement in a hypertension and diabetes prevention research program: Description and lessons learned

Abstract: Background Stakeholder engagement is important from the management point of view to capture knowledge, increase ownership, reduce conflict, encourage partnership, as well as to develop an ethical perspective that facilitates inclusive decision making and promotes equity. However, there is dearth of literature in the process of stakeholder engagement. The purpose of this paper is to describe the process of increasing stakeholder engagement and highlight the lessons learnt on stakeholder engagement while designi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[12][13][14][15] In Nepal, this collaboration was meaningful in the hypertension and diabetes prevention research program. 16 Fostering bridges between researchers and policymakers enhances understanding and knowledge. 17 Trust is crucial for building respectful relationships, enabling effective collaboration, and connecting relevant evidence to policymakers.…”
Section: Strengthening the Research-policy Interfacementioning
confidence: 99%
“…[12][13][14][15] In Nepal, this collaboration was meaningful in the hypertension and diabetes prevention research program. 16 Fostering bridges between researchers and policymakers enhances understanding and knowledge. 17 Trust is crucial for building respectful relationships, enabling effective collaboration, and connecting relevant evidence to policymakers.…”
Section: Strengthening the Research-policy Interfacementioning
confidence: 99%
“…Two described or guided the process of translating research into practice 9,34 These articles reported identification, process, and outcome of stakeholder engagement. 9,34 Twelve research were conducted to understand what influenced implementation.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Two described or guided the process of translating research into practice 9,34 These articles reported identification, process, and outcome of stakeholder engagement. 9,34 Twelve research were conducted to understand what influenced implementation. [18][19][20][22][23][24][25][26][27][28]31,37 However, many of these articles are not specific to an EBP or implementation strategies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-adherence to chronic medication is a complex issue that affects clinical outcomes,4 health expenditure and the health system’s operation 5 6. Several implementation research studies have revealed that it is imperative to involve the relevant stakeholders to recommend interventions effectively and agree on long-term decisions to improve patient compliance 7–9…”
Section: Introductionmentioning
confidence: 99%